2018
DOI: 10.3390/genes9020110
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the GRF Family Reveals Their Involvement in Abiotic Stress Response in Cassava

Abstract: GENERAL REGULATORY FACTOR (GRF) proteins play vital roles in the regulation of plant growth, development, and response to abiotic stress. However, little information is known for this gene family in cassava (Manihot esculenta). In this study, 15 MeGRFs were identified from the cassava genome and were clustered into the ε and the non-ε groups according to phylogenetic, conserved motif, and gene structure analyses. Transcriptomic analyses showed eleven MeGRFs with constitutively high expression in stems, leaves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
3
14
1
Order By: Relevance
“…Genes with fewer introns can be transcribed faster to cope with various external stresses such as pathogenic and heat shock stress [30,50]. Similar studies have been reported in the leucine-rich repeat family [51] and the GRF family [52]. In our study, only two genes (Bol029467 and Bol007321) contained longer introns, whereas the other genes contained only one or no intron.…”
Section: Discussionsupporting
confidence: 89%
“…Genes with fewer introns can be transcribed faster to cope with various external stresses such as pathogenic and heat shock stress [30,50]. Similar studies have been reported in the leucine-rich repeat family [51] and the GRF family [52]. In our study, only two genes (Bol029467 and Bol007321) contained longer introns, whereas the other genes contained only one or no intron.…”
Section: Discussionsupporting
confidence: 89%
“…These GRF family genes were divided into two groups (I and II) and five subgroups (from G1 to G5 subgroups) (Fig. 3), which is similar to the previous results (Kim et al 2003;Cao et al 2016;Shang et al 2018). The G4 and G5 subgroups belonged to the I group, and the G1, G2 and G3 subgroups were clustered in the II group.…”
Section: Phylogenetic Relationships Of Grf Proteins From a Thaliana And F Vescasupporting
confidence: 86%
“…3c). The conserved structure of GmGRFs was similar to those from other plant species, in which most genes contained three introns [29][30][31]. The lengths of individual GmGRFs were variable in intron length could partly reflect the length of different genes.…”
Section: Structural Analysis Of Gmgrfsmentioning
confidence: 54%